2015
DOI: 10.1155/2015/628192
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Neuroinflammation in Parkinson’s Disease: From Biomarkers to Anti-Inflammatory Based Therapies

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide, being characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Among several putative factors that may contribute to PD pathogenesis, inflammatory mechanisms may play a pivotal role. The involvement of microglial activation as well as of brain and peripheral immune mediators in PD pathophysiology has been reported by clinical and experimental studies. These inflammatory biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
125
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 114 publications
2
125
0
2
Order By: Relevance
“…Multiple immunological stimuli have been shown to trigger microglial activation leading to sustained chronic inflammation in dopaminergic neurodegenerative processes (Hirsch et al, 2013; Hirsch et al, 2012; Rocha et al, 2015). In this study, we investigated the role of PKCδ signaling in regulating microglial activated-inflammatory responses and its relationship to dopaminergic neurotoxicity in both cell culture and murine models of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple immunological stimuli have been shown to trigger microglial activation leading to sustained chronic inflammation in dopaminergic neurodegenerative processes (Hirsch et al, 2013; Hirsch et al, 2012; Rocha et al, 2015). In this study, we investigated the role of PKCδ signaling in regulating microglial activated-inflammatory responses and its relationship to dopaminergic neurotoxicity in both cell culture and murine models of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines represent the major inflammatory mediators in the CNS that most often act through specific receptor-mediated mechanisms, thereby triggering the activation of downstream signaling cascades (Rocha et al, 2015). In the CNS, activated microglia produce numerous inflammatory cytokines including TNFα, IL-1β, and IL-6, which play a central role in initiating the proinflammatory response (Sadasivan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that neuroinflammation plays a critical role in the pathogenesis of neurodegenerative diseases, including PD [22,23,24,25]. Neuroinflammatory mechanisms might contribute to a cascade of events that result in the progressive degeneration and/or death of neuron cells in PD [22].…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of microglia and overproduction of proinflammatory factors lead to the death of DA neurons. Inhibition of microglia activation could inhibit the production of proinflammatory factors, thereby protecting the brain from parkinsonism [24,25]. Thus, it is very important to regulate the function of microglia during the progress of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained microglial and astroglial activation near dying dopaminergic neurons in the SNpc is evident in PD patients and animal models of the disease (McGeer et al, 1988; Hirsch and Hunot, 2009). Several in vitro cell culture and in vivo animal studies have demonstrated the elevation of key enzymes involved in the production of reactive oxygen species (ROS) due to mitochondrial impairment and reactive nitrogen species (RNS) in dopaminergic neurons of the SN, including microglial gp91phox (Nox2) and inducible nitric oxide synthase (iNOS) (Gao et al, 2003b; Wu et al, 2003; Hunter et al, 2007; Hirsch et al, 2012; Murakami and Hirano, 2012; Strowig et al, 2012; Yan et al, 2014; Rocha et al, 2015). In addition, different pro-inflammatory cytokines, including tumor necrosis factor alpha (TNF-α), interleukins IL-1β and IL-6, interferon gamma (IFN-γ), as well as other immune neurotoxins, are found either in the CSF or affected regions of PD brains (Nagatsu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%